International Group Exhibition - Audio Visual Arts Festival Ionios Parliament - Antoniou, Klitsa (My University, 2026)
International Group Exhibition - Audio Visual Arts Festival Ionios Parliament Ionian University - Department of Audio and Visual Arts Curated by Aggelos Floros and Sophia Paschou Corfu, Kerkira, Greece